The Political Economy of Good Governance - Asefa, Sisay (W.E. Upjohn Institute, 2015)
The contributors to this book capture several of the key dimensions of good governance, as well as what deleterious and negative consequences may arise in its absence. They draw analysis and solutions from diverse sectors such as economics, public administration, management, and political science, in order to treat some of the most pressing societal issues of our time. They connect the importance of education, health, climate change, and poverty to address the challenges of creating a world where more countries embrace good governance policies to benefit their peoples.